Isolation Of Moringa Leaf Flavonoids (Moringa Oleifera L.) Using Column Chromatography - Sa'adah, Anifatus; Ovikariani (Science and Community Pharmacy Journal, 2023)
Preface : Moringa oleifera L. is one plant that contains secondary metabolite compounds such as alkaloids, steroids, tannins, saponins, anthraquinones, terpenoids, and flavonoids. Flavonoids donate their hydroxyl groups to inhibit free radicals. Purpose :This study aimed to isolate flavonoid compounds from Moringa leaf ethanol extract. Method : Extraction was carried out by maceration method and continued isolation using Column Chromatography method with n-butanol: acetic acid: water (4: 1: 5) eluent. Isolate results were identified by TLC, spectro, and FTIR. Result : FTIR analysis on fraction 5 contains flavonoid derivative compounds. Conclusion : It is flavonols with a purity of quercetin of 77.99%.